Mechanism of improved electromigration reliability using Fe-Ni UBM in wafer level package. Issue 8 (August 2018) - Gao, Li-Yin; Zhang, Hao; Li, Cai-Fu; Guo, Jingdong; Liu, Zhi-Quan
Abstract: Fe-Ni films with compositions of 73 wt% of Ni and 45 wt% of Ni were used as under bump metallization (UBM) in wafer level chip scale package, and their reliability was evaluated through electromigration (EM) test compared with commercial Cu UBM. For Sn3.8Ag0.7Cu(SAC)/Cu solder joints, voids had initiated at Cu cathode after 300 h and typical failures of depletion of Cu cathode and cracks were detected after 1000 h EM. While the SAC/Fe-Ni solder joints kept at a perfect condition without any failures after 1000 h EM. Moreover, the characteristic lifetime calculated by Weibull analysis for Fe-73Ni UBM (2121 h), Fe-45Ni UBM (2340 h) were both over three folds to Cu UBM's (698 h). The failure modes for Fe-Ni solder joints varied with the different growth behavior of intermetallic compounds (IMCs), which can all be classified as the crack at the cathodic interface between solder and outer IMC layer. The atomic fluxes concerned cathode dissolution and crack initiation were analyzed. When Fe-Ni UBM was added, cathode dissolution was suppressed due to the low diffusivity of IMCs and opposite transferring direction to electron flow of Fe atoms. The smaller EM flux within solder material led a smaller vacancy flux in Fe-Ni solder joints, which can explain the delay of solder voids and cracks as well as the much longer lifetime under EM.